Ca2+ adsorption to lipid membranes and the effect of cholesterol in their composition - Raffo Iraolagoitia, Ximena Lucía (2010)
The aim of this work is to determine the binding of ionic calcium (Ca2+) to lipid membranes in which the availability of the phosphate groups to the aqueous phase is modified by the degree of saturation of the lipids and the inclusion of cholesterol. The shifts in the phosphate bands observed in the Fourier transform infrared spectroscopy (FTIR) spectra are direct evidence of the interaction of Ca2+ with phosphate groups. The binding analysis was done by determining the changes in the zeta potential of liposomes suspended in buffer at controlled temperature. The changes produced by the ion on the zeta potential of dioleoylphosphatidylcholine (DOPC); dipalmitoylphosphatidylcholine (DPPC); distearoylphosphatidylcholine (DSPC); dimyristoylphosphatidylethanolamine (DMPE) and their mixers with cholesterol were measured, showing a Langmuir isotherm behavior in all the lipid composition assayed. The results show that the interaction of Ca2+ to lipid membranes depends on the exposure and the density of phosphate groups at the membrane interphase.